The evolving role of dendritic cells in atherosclerosis - Britsch, Simone; Langer, Harald; Dürschmied, Daniel; Becher, Tobias (International journal of molecular sciences, 2024)
Atherosclerosis, a major contributor to cardiovascular morbidity and mortality, is characterized by chronic inflammation of the arterial wall. This inflammatory process is initiated and maintained by both innate and adaptive immunity. Dendritic cells (DCs), which are antigen-presenting cells, play a crucial role in the development of atherosclerosis and consist of various subtypes with distinct functional abilities. Following the recognition and binding of antigens, DCs become potent activators of cellular responses, bridging the innate and adaptive immune systems. The modulation of specific DC subpopulations can have either pro-atherogenic or atheroprotective effects, highlighting the dual pro-inflammatory or tolerogenic roles of DCs. In this work, we provide a comprehensive overview of the evolving roles of DCs and their subtypes in the promotion or limitation of atherosclerosis development. Additionally, we explore antigen pulsing and pharmacological approaches to modulate the function of DCs in the context of atherosclerosis.
Gesehen am 11.03.2025
Dieser Artikel gehört zum Special issue: Molecular mechanisms and pathophysiology of atherosclerosis 2.0